2005
DOI: 10.1007/s10342-005-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold storage treatments and transplanting stress on gas exchange, chlorophyll fluorescence and survival under water limiting conditions of Pinus radiata stock-types

Abstract: Effect of cold storage treatments and transplanting stress on gas exchange, chlorophyll fluorescence and survival under water limiting conditions of Pinus radiata stock-types Abstract The capacity of radiata pine seedlings to overcome planting shock in wet and dry conditions and their dependence on previous history was analysed by studying post-planting resumption of gas exchange and photochemical reactions, and survival 2 months later. Even under well-irrigated soil conditions, seedlings showed the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…We did not observe a significant linear relationship between δ 13 C and Y traits. Although previous studies reported δ 13 C to be negatively associated with Y ( Mena-Petite et al, 2000 , 2005 ; Dias and Brüggemann, 2010 ), Y was a poor predictor of water stress tolerance across the 63 families we tested. The poor predictability of Y in our study could be due to several reasons.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…We did not observe a significant linear relationship between δ 13 C and Y traits. Although previous studies reported δ 13 C to be negatively associated with Y ( Mena-Petite et al, 2000 , 2005 ; Dias and Brüggemann, 2010 ), Y was a poor predictor of water stress tolerance across the 63 families we tested. The poor predictability of Y in our study could be due to several reasons.…”
Section: Discussioncontrasting
confidence: 60%
“…Unlike other studies, this study maintained the potting medium to a constant 22–25% WHC. The strong relationship between δ 13 C and Y determined by Mena-Petite et al (2005) was obtained from Y measurements collected over a wide range of foliar relative water potential (∼25–85% range) after withholding irrigation over a short-term period. However, a small number of Y values in this study were below 0.70.…”
Section: Discussionmentioning
confidence: 99%
“…Under water stress, the deprivation of CO 2 at the chloroplast level by stomata closure could enhance the sensitivity of the photosynthetic apparatus to photoinhibition (Escalona et al 1999). It has been observed that as drought stress rises, a significant alteration occurs in all fluorescence parameters (Mena-Petite et al 2005). In our experiments, photochemical efficiency was only slightly reduced by water stress and only after 16 d of water deprivation, and this injury was delayed when plants were grown at EC.…”
Section: Discussionmentioning
confidence: 83%
“…As water potential becomes more negative, other physiological symptoms appear like reduced stomatal conductance, photosynthesis, transpiration and growth (Grossnickle, 1988;Guehl et al, 1989;Jacobs et al, 2009;Sands, 1984). These symptoms were observed by Mena-Petite et al (2005) after transplanting seedlings of Pinus radiata both under drought and under well-watered conditions. Reduced leaf area, leaf shedding, shoot growth and needle length area are the principal morphological symptoms (Haase & Rose, 1993;Struve & Joly, 1992).…”
Section: Problems During the Forest Establishmentmentioning
confidence: 98%